Nomenclatural type of Torminalis glaberrima, current name for the species traditionally known as Sorbus torminalis (Rosaceae) - Ferrer-Gallego, Pedro Pablo (UMA Editorial, 2024)
The name Torminalis glaberrima (Rosaceae), based on the Gandoger’s name Sorbus glaberrima, is discussed and typified. Torminalis glaberrima is the current name of the species traditionally known as Sorbus torminalis. A lectotype is selected from a specimen preserved in the Claude Bernard Univsersity Lyon 1 Herbarium at LY.

Se discute y tipifica el nombre Torminalis glaberrima (Rosaceae), basado en el nombre de Gandoger Sorbus glaberrima. Torminalis glaberrima es el nombre actual de la especie tradicionalmente conocida como Sorbus torminalis. Se selecciona un lectotipo a partir de un espécimen conservado en el Herbario Claude Bernard Univsersity Lyon 1 en LY.
Keywords: Rosáceas; Árboles - Terminología; Crataegus torminalis; Gandoger; Lectotype; Nomenclature; Sorbus glaberrima; Tautonym